Does local religiosity affect organizational risk-taking? Evidence from the hedge fund industry - Gao, Lei; Wang, Ying; Zhao, Jing (Journal of Corporate Finance, 2017)
We examine the impact of local religious beliefs on organizational risk-taking behaviors using hedge funds as a new and unique setting. We find robust evidence that local religiosity is significantly negatively related to both total and idiosyncratic volatilities of hedge funds during 1996–2013. This relation is primarily driven by semi-directional funds, reversed for directional funds, and nonexistent for non-directional funds. Consistent with the local preference channel, the impact of local religiosity on risk-taking is only pronounced among funds for which local managers and investors are economically more important, namely young and small funds. Further, hedge funds located in more religious counties tend to hold less risky stocks and diversify their stock portfolios across industries, thus contributing to lower hedge fund risk-taking. Overall, our evidence suggests that local culture, in particular religiosity, may motivate hedge fund managers to reduce risk.